Entre fases: práticas informacionais durante a menopausa - Andrikonis, Juliana Buzinaro (Universidade Federal de São Carlos, 2025)
The presented dissertation focuses on investigating the information practices of women experiencing at least one perimenopausal stages, a process that approximately 18% of the Brazilian population has gone through or will go through, and which is an expected experience for all cisgender women. Despite its recurrence, the perimenopause is still surrounded by insecurities and uncertainties, especially regarding the management of symptoms that affect quality of life, such as hot flashes, insomnia, and emotional changes, as well as controversies surrounding hormone replacement therapy. The scarcity of accessible information and the persistence of taboos on the subject exacerbate these challenges, making it difficult for women to access resources that could help them better navigate this phase. In this context, this research aims to identify the informational practices of these women, contributing to an interdisciplinary understanding between Information Science and the Health field. To support the study, we rely on four theories from Information Science: Brenda Dervin’s Sense-Making approach, which explores how individuals construct meaning in situations of uncertainty; Reijo Savolainen’s Everyday Life Information Seeking model, which focuses on how people seek information in their daily lives; Elfreda Chatman’s Small World concept, which analyzes how groups of individuals share information in specific environments; and finally, Pamela McKenzie’s informational practices approach, which examines how people interact with information in their social context. The research adopts a descriptive, exploratory, and cross-sectional approach, with qualitative data collection through the survey method, using a questionnaire. In addition to primary data collection, bibliographic materials were used, obtained from guidance recommendations, references from foundational works, and searches in scientific databases such as Scopus, PubMed, SciELO, and Web of Science, using search expressions specifically developed for this study. The results are based on 208 valid responses, with most participants located in the state of São Paulo, identifying as white, and holding postgraduate degrees. Although the majority of respondents belong to a socially privileged group, we also obtained responses from women with different socioeconomic backgrounds, enriching the findings. These results suggest that many women indeed experience doubts, difficulties in accessing evidence-based health information, and insecurities during the perimenopausal phase. Among them, most seek guidance from healthcare professionals to address these concerns. However, some respondents expressed frustration with the lack of adequate attention and the inability of healthcare professionals to provide proper guidance. Another significant finding is that women frequently turn to other women for information about menopause, whether through virtual groups, friends, or family members. This study leads us to conclude that the healthcare field could greatly benefit from integrating information services through the lens of Information Science. This approach would provide more adequate support for individuals in various health situations, especially for those experiencing some degree of social vulnerability.
Between phases: informational practices during menopause
Keywords: Práticas informacionais; Mulheres; Informação em saúde; Menopausa; Climatério; Information practices; Women; Health information; Menopause; Climacteric; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO